INFLUENCE OF THE PROCESSING STEPS ON CASHEW NUT QUALITY - CAVALCANTE, CARLOS ELIARDO BARROS; SOARES, DENISE JOSINO; MAIA, GERALDO ARRAES; DE SOUSA, PAULO HENRIQUE MACHADO; DE FIGUEIREDO, RAIMUNDO WILANE; CONSTANT, PATRÍCIA BELTRÃO LESSA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
Cashew nuts have high nutritional value. This nut provides macronutrients, micronutrients and a large variety of antioxidants, such as phenolic compounds. There are losses in some compounds during the processing of fruits and there are very few studies on this aspect. Given the above, this research aimed to determine the eff ect of the processing steps on cashew nut characteristics with emphasis on total antioxidant activity. Signifi cant diff erences were observed between the processing steps for all the chemical and physical-chemical characteristics studied. Cashew nuts contained high levels of lipids and energy, low content of moisture and water activity and medium content of phenolic compounds (51.33 GAE/100 g) and antioxidant activity by the ABTS•+ radical (6.49 μM Trolox/g) at the end of the process. Regarding the total antioxidant activity, it was observed that the ABTS•+ radical method can be considered appropriate to measure the antioxidant activity of cashew nuts, since the results presented lower coeffi cients of variation and express proportionate results to other methods.